46 Grouping of procedures improves catheterisation laboratory efficiency – a single centre experience. (28th September 2016) - McInerney, A; Power, C; Geraghty, S; Morgan, T; McEvoy, D; Collins, L; Gumbrielle, T
Abstract : Introduction: Improving Catheterisation Laboratory efficiency is the aim of all Cardiology Departments. Marrying efficiency with patient satisfaction is often challenging. Implantable loop recorder (ILR) insertion is a common procedure in our institution. To date, most ILR implantations have taken place on an ad hoc basis. We had long surmised that procedure efficiency could be improved by grouping implants on the same day without compromising patient experience. Our study aimed to prove this theory using ILR as an index procedure. Methods: Two half-days were set aside for implantation. Patients were unselected and taken from the waiting list. All implants were planned as day cases. 12 were planned for day 1 and 18 for day 2. Patients were admitted to the cardiology day ward (CDW) on the morning of the procedure. Antibiotics and paracetamol were administered as per protocol. Patient education, given by the CDW nurses, included pros and cons of sedation, the method of implantation and wound care. Home monitoring education was given by the manufacturing company representative. A team meeting including the Consultant, Nursing staff, and Cardiac Physiologists took place after the first day to highlight possible changes for day 2. On both days all patients were asked to complete a questionnaire regarding their experience. Results: 11 patients were implanted and one had device removal on day 1 with 14 implants and 4 removals on day 2. The average age was 57. Indications were syncope (13), palpitations (9) and stroke (3). All patients opted to have no sedation. All procedures were carried out by a single operator. The average procedure duration was 8 minutes (range 4–15 minutes). All patients were discharged from the CDW within 30 minutes following the procedure. Following the team meeting on day 1, it was decided that paracetamol should be administered orally rather than intravenously, procedure packs were pre-prepared and further improvements in CDW utilisation were made. This resulted in further improvement in the time taken per patient from admission to discharge. All implants had adequate p wave and r wave amplitudes as per manufacturers recommendations. No patients were readmitted with device related complications. 93.3% of patients returned their patient experience questionnaire. 100% were overall satisfied with the service. 100% either strongly agreed, or agreed, that their stay was completed in a timely and efficient manner. 100% either strongly agreed, or agreed, they were treated respect at all times and 100% either strongly agreed, or agreed, that they were satisfied with discharge information received. Conclusion: Continuous appraisal of CDW and catheterisation lab patient flow highlights areas of inefficiency. Our study demonstrates that improvements can be made by grouping procedures on a single day. Numerous factors contributed to the success of our study including clearly defined roles for staff, good patient education, involvement of device manufacturers representatives and having the procedure performed by a single primary operator. The high levels of patient satisfaction with the care they received, proves that increased efficiency does not have to compromise patient experience.